Pengaruh Model Pembelajaran Open -Ended Berbantuan Media Sanakpilian Terhadap Kemampuan Berfikir Kritis Matematika - Aisyah, Irma Antonia; Mardiana, Tria; Hajron, Kun Hisnan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of theLearning Model with the Open-endedhelp of relatives on the ability to think critically in mathematics in fourth grade studentsof SDN Dukun 02, Magelang district.This study uses a pre-experimental design with a one group pretest posttest designmodel. Research subjects were selected by non- probability sampling saturated samplingmodel. Samples were taken as many as 15 students, using data collection methods in theform of description tests and performance tests of students' critical thinking skills.prerequisite test for critical thinking skills using theformula. The Kolmogorov Smirov,validity test for the description test uses theformula Pearson. Reliability test usingformulacornbach's alpha with the help of SPSS For Windows. In addition, the researchers alsoused the level of difficulty test and the test of discriminating power. Analysis of the datausingstatistical techniques, non-parametric namely by using Wilcoxon test.The results showed that the calculation of the average value of the posttestdescription test was 71.25 which was greater than the pretest value with an average valueof 48.75, the calculation of performance assessment in the pretest activity was 65 and theposttest was 72.5. this is evidenced by the results of the Microsoft excel and the next resultof the Wilcoxon test analysis with a significant value of 0.01 <0.05, which means thatthere is a significant difference between the results of the pretest and posttest using anopen ended learning model assisted by relatives' media. The results of this study can beconcluded that the use of sanakpilian media assisted by sanakpilian media has asignificant effect on students' critical thinking skills in learning mathematics.